Tourism and Foreign Language Training for Local Merchants and Guides in Penglipuran Tourism Village of Bangli Regency - Dian Pramita Sugiarti; Ni Made Verayanti Utami; Kadek Apriliani (Politeknik Negeri Bali, 2018)
Community service in form of practical tourism and foreign language training for local merchants and guides in Penglipuran tourist village, Bangli regency was aimed at improving the knowledge of Japanese tourism and vocabulary and English in accordance with the appropriate grammar. The targets in this training were local merchants and guides in Penglipuran village who had less knowledge about tourism and the proper usage of foreign language. Not only the training of tourism and practical foreign languages, local merchants and guides were also given knowledge about the characteristics of domestic and international tourists, as well as ways of serving the tourists in accordance with the agreed standards. The special target of this dedication was to find a social formula to solve the problems that occurred in the tourist village of Penglipuran. The fostering system implemented so far was less effective so that it led to a decline in knowledge about tourism and foreign languages for local merchants and guides who were the tourism actors expected to provide correct information to the tourists. If this was left unchecked, the number of tourist arrivals and local merchants and guides who had international standard capability would continue to decrease annually. The method of devotion used was the workshop and FGD so that the results of teaching could be understood by Penglipuran village management to continue to conduct trainings that educate local merchants and guides.